Randomised clinical trial: mesalazine and/or probiotics in maintaining remission of symptomatic uncomplicated diverticular disease – a double‐blind, randomised, placebo‐controlled study. Issue 7 (19th August 2013) - Tursi, A.; Brandimarte, G.; Elisei, W.; Picchio, M.; Forti, G.; Pianese, G.; Rodino, S.; D'Amico, T.; Sacca, N.; Portincasa, P.; Capezzuto, E.; Lattanzio, R.; et al.
Summary Background Placebo‐controlled studies in maintaining remission of symptomatic uncomplicated diverticular disease (SUDD) of the colon are lacking. Aim To assess the effectiveness of mesalazine and/or probiotics in maintaining remission in SUDD. Methods A multicentre, double‐blind, placebo‐controlled study was conducted. Two hundred and ten patients were randomly enrolled in a double‐blind fashion in four groups: Group M (active mesalazine 1.6 g/day plus Lactobacillus casei subsp. DG placebo), Group L (active Lactobacillus casei subsp. DG 24 billion/day plus mesalazine placebo), Group LM (active Lactobacillus casei subsp. DG 24 billion/day plus active mesalazine), Group P (Lactobacillus casei subsp. DG placebo plus mesalazine placebo). Patients received treatment for 10 days/month for 12 months. Recurrence of SUDD was defined as the reappearance of abdominal pain during follow‐up, scored as ≥5 (0: best; 10: worst) for at least 24 consecutive hours. Results Recurrence of SUDD occurred in no (0%) patient in group LM, in 7 (13.7%) patients in group M, in 8 (14.5%) patients in group L and in 23 (46.0%) patients in group P (LM group vs. M group, P = 0.015; LM group vs. L group, P = 0.011; LM group vs. P group, P = 0.000; M group vs. P group, P = 0.000; L group vs. P group, P = 0.000). Acute diverticulitis occurred in six group P cases and in one group L case (P = 0.003). Conclusion Both cyclic mesalazine and Lactobacillus casei subsp. DG treatments, particularly when given in combination, appear to be better than placebo for maintaining remission of symptomatic uncomplicated diverticular disease. (ClinicalTrials.gov: NCT01534754).